TEACHER AND STUDENT ETHICS BASED ON ISLAMIC EDUCATION PERSPECTIVE - Selvi Regita; Aprilia Aprilia (Proceeding International Seminar of Islamic Studies, 2022)
Ethics is seen as something that is very important and upheld, and must exist in everyone, especially the ethics of teachers and students. Ethics Based on Islamic teachings, it is carried out through Islamic education in the form of directing the development of life and religion to students towards the ideals of Islamic life. However, lately ethical issues in the world of education seem to have been sidelined by teachers and students. The transformation of knowledge that leads to the improvement of intellectual abilities is prioritized. Meanwhile, the internalization of spiritual and ethical values does not receive priority and is not placed in the highest position. This study discusses Teacher and Student Ethics Based on Islamic Teachings. This research uses library research. This study uses library materials as the main data source, in this study the data sources were taken from books and journals related to the research title. The results showed: The ethics that the teacher had to do were to accept the questions asked by the students, sit with dignity and calm, not be arrogant about their knowledge, give priority to tawadhu'in meeting places and assemblies, not allowed to use words or sentences or utterances. Bad, showing affection to students while teaching. And the ethics that must be done by students are, should not be arrogant, be humble to the teacher, be patient by not being angry, not easily discouraged, not in a hurry to ask questions or interrupt the teacher's conversation before being allowed to speak even in class discussions, husnudzonto the teacher even though the teacher does things against his instincts, obeys the teacher's orders while still in good terms.